Durable Red Blood Cell Transfusion Independence in a Patient with an MDS/MPN Overlap Syndrome Following Discontinuation of Iron Chelation Therapy - Harpreet Kochhar; Chantal S. Leger; Heather A. Leitch (Case Reports in Hematology)
Background. Hematologic improvement (HI) occurs in some patients with acquired anemias and transfusional iron overload receiving iron chelation therapy (ICT) but there is little information on transfusion status after stopping chelation. Case Report. A patient with low IPSS risk RARS-T evolved to myelofibrosis developed a regular red blood cell (RBC) transfusion requirement. There was no response to a six-month course of study medication or to erythropoietin for three months. At 27 months of transfusion dependence, she started deferasirox and within 6 weeks became RBC transfusion independent, with the hemoglobin normalizing by 10 weeks of chelation. After 12 months of chelation, deferasirox was stopped; she remains RBC transfusion independent with a normal hemoglobin 17 months later. We report the patient’s course in detail and review the literature on HI with chelation. Discussion. There are reports of transfusion independence with ICT, but that transfusion independence may be sustained long term after stopping chelation deserves emphasis. This observation suggests that reduction of iron overload may have a lasting favorable effect on bone marrow failure in at least some patients with acquired anemias.